SECURITY AND MINORITIES: BUILDING A HUMAN SECURITY INDEX FOR MINORITY ISSUES - Andrea Carlà (Bezbednosni Dijalozi, 2023)
Security has become a recurring theme when addressing minority issues. Though minorities are often perceived as raising security concerns, the fundamental task is to ask ‘security for whom?’ and reflect on what in society really needs to be secured. Addressing this question, this paper analyses minority issues in terms of ‘human security’, putting people at the heart of security practices. Human security regards the need to guarantee the wellbeing of individuals, providing ‘freedom from fear,’ ‘freedom from want’ and ‘human dignity,’ and responding to people’s needs in dealing with sources of domestic and global threats. I argue that a human security approach provides several insights to better deal with minority concerns, adding to the traditional goal of recognizing civil, political and cultural rights, a more comprehensive, holistic understanding of the needs and challenges faced by members of minorities. It addresses minority rights and protection in the full context of their lives, broadening the arenas of action in which one can (and should) intervene. However, human security is a vague term that is not clearly operationalized. In this light, the paper aims at developing an innovative human security index that applies specifically to cultural diversity issues and majority-minority relations and allows to measure the degree of human security provided to minorities.